p53 prevents neurodegeneration by regulating synaptic genes. - Merlo, P.; Frost, B.; Peng, S.; Yang, Y.J.; Park, P.J.; Feany, M. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
DNA damage has been implicated in neurodegenerative disorders, including Alzheimer's disease and other tauopathies, but the consequences of genotoxic stress to postmitotic neurons are poorly understood. Here we demonstrate that p53, a key mediator of the DNA damage response, plays a neuroprotective role in a Drosophila model of tauopathy. Further, through a whole-genome ChIP-chip analysis, we identify genes controlled by p53 in postmitotic neurons. We genetically validate a specific pathway, synaptic function, in p53-mediated neuroprotection. We then demonstrate that the control of synaptic genes by p53 is conserved in mammals. Collectively, our results implicate synaptic function as a central target in p53-dependent protection from neurodegeneration.